Reduction of seizure frequency after epilepsy surgery in a patient with STXBP1 encephalopathy and clinical description of six novel mutation carriers. Issue 5 (14th February 2013) - Weckhuysen, Sarah; Holmgren, Philip; Hendrickx, Rik; Jansen, Anna C.; Hasaerts, Daniele; Dielman, Charlotte; de Bellescize, Julitta; Boutry‐Kryza, Nadia; Lesca, Gaetan; Spiczak, Sarah Von; Helbig, Ingo; Gill, Deepak; et al.
Summary Mutations in STXBP1 have been identified in a subset of patients with early onset epileptic encephalopathy (EE), but the full phenotypic spectrum remains to be delineated. Therefore, we screened a cohort of 160 patients with an unexplained EE, including patients with early myoclonic encephalopathy (EME), Ohtahara syndrome, West syndrome, nonsyndromic EE with onset in the first year, and Lennox‐Gastaut syndrome (LGS). We found six de novo mutations in six patients presenting as Ohtahara syndrome (2/6, 33%), West syndrome (1/65, 2%), and nonsyndromic early onset EE (3/64, 5%). No mutations were found in LGS or EME. Only two of four mutation carriers with neonatal seizures had Ohtahara syndrome. Epileptic spasms were present in five of six patients. One patient with normal magnetic resonance imaging (MRI) but focal seizures underwent epilepsy surgery and seizure frequency dropped drastically. Neuropathology showed a focal cortical dysplasia type 1a. There is a need for additional neuropathologic studies to explore whether STXBP1 mutations can lead to structural brain abnormalities.